A novel pre-processing inspection methodology to enhance productivity in automotive product remanufacture: An industry-based research of 2196 engines - Sara J. Ridley; W. L. Ijomah (Journal of Remanufacturing, 2015)
Remanufacture, a process of returning used products to 'as-new' condition with matching guarantee, is commercially viable where the remaining value in the used product and the final selling price are much higher than the cost of the products' rebuilding. Guide identified that remanufacturers perceive the scarcity of effective remanufacturing tools and techniques as a key threat to the industry whilst Ijomah assessed the key remanufacturing issues on a five-point scale ranging from 'Not Significant through to 'Critical'. Component inspection was the only issue rated as 'critical' by all remanufacturers. Extensive work within the industry plus the detailed analysis and observation of the remanufacturing process during this research has shown that component inspection has significant bearing on overall productivity. However, the activity is undertaken in a hap-hazard manner based almost purely on experience and guesswork and lacks proper methodologies and tools. This paper presents the results of quantitative research, conducted in a Caterpillar UK Remanufacturing facility, to establish the relationship between pre-processing inspection and the subsequent remanufacturing process time for returned cores (used products).
Keywords: 650; Remanufacturing; Pre-processing; Inspection methodology